2023
DOI: 10.1039/d3ta03613h
|View full text |Cite
|
Sign up to set email alerts
|

Large mass field fluctuation and lattice anharmonicity effects promote thermoelectric and mechanical performances in NbFeSb half-Heusler alloys via Ti/Zr/Hf stepwise doping

Abstract: Thermoelectric materials require not only high performance to maximize the energy conversion efficiency but also good mechanical properties to guarantee machinability and reliable operation. In this work, multi-element doping NbFeSb-based...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…When x = 0.03, this parameter for the doped samples reaches the lowest value of 0.48 W/m·K, which approaches the amorphous limit of lattice thermal conductivity (0.395 W/m·K) of BaScCuTe 3 estimated from the Cahill model. To further understand the origin of ultralow lattice thermal conductivity, sound velocity for BaScCuTe 3 and some state-of-art thermoelectric materials are provided for comparison (Table and Figure (c)). In addition to the well-known half-Heusler alloy and skutterudite, other high-performance thermoelectric compounds all show low sound velocity and low lattice thermal conductivity, due to weak chemical bonding and the small phonon mean free path …”
Section: Resultsmentioning
confidence: 99%
“…When x = 0.03, this parameter for the doped samples reaches the lowest value of 0.48 W/m·K, which approaches the amorphous limit of lattice thermal conductivity (0.395 W/m·K) of BaScCuTe 3 estimated from the Cahill model. To further understand the origin of ultralow lattice thermal conductivity, sound velocity for BaScCuTe 3 and some state-of-art thermoelectric materials are provided for comparison (Table and Figure (c)). In addition to the well-known half-Heusler alloy and skutterudite, other high-performance thermoelectric compounds all show low sound velocity and low lattice thermal conductivity, due to weak chemical bonding and the small phonon mean free path …”
Section: Resultsmentioning
confidence: 99%
“…In particular, Nb 0.82 Ti 0.06 Zr 0.06 Hf 0.06 FeSb exhibited the highest PF value of 40.3 μW cm −1 K −2 at 973 K and achieved the lowest lattice k of 3.6 W m −1 K −1 at 973 K, which was approximately half that of pristine NbFeSb. Consequently, Nb 0.82 Ti 0.06 Zr 0.06 Hf 0.06 FeSb achieved a high ZT value of 0.74 at 973 K and maintained an average ZT of 0.45 ranging from 333 K to 973 K. 174 Zhang et al have also applied the entropy-driven concept on a Hf-free HH compound and found a k of 3.14 W m −1 K −1 at 870 K and a very low k l of 0.48 W m −1 K −1 at 870 K of Ti 0.57 Zr 0.4 Al 0.02 Ta 0.01 NiSn 0.98 Sb 0.02 , which represents an 82.3% decrease compared to that of pristine TiNiSn. As a result, ZT has risen from 0.67 for TiNiSn to ∼1.4 for Ti 0.57 Zr 0.4 Al 0.02 Ta 0.01 NiSn 0.98 Sb 0.02 at 870 K, resulting in an increase of almost 108% that was accomplished through entropy engineering.…”
Section: Overview Of High-entropy Thermoelectric Materialsmentioning
confidence: 92%
“…6B 3 ), nearly five times that of Ti 2 FeNiSb 2 . 173 Tan et al 174 have designed multi-element-doped NbFeSb-based alloys by introducing Ti, Zr, and Hf atoms into the Nb sites through a stepwise doping process. This doping resulted in an increase in the n-type hole-carrier concentration and an enhancement in electrical transport properties.…”
Section: Overview Of High-entropy Thermoelectric Materialsmentioning
confidence: 99%